Luteolin attenuated cisplatin-induced cardiac dysfunction and oxidative stress via modulation of Keap1/Nrf2 signaling pathway. (1st February 2022) - Qi, Yajun; Fu, Shuang; Pei, Donggen; Fang, Qilu; Xin, Wenxiu; Yuan, Xiaohong; Cao, Yingying; Shu, Qi; Mi, Xiufang; Luo, Fang
Abstract: Cardiovascular complications are a well-documented limitation of cancer chemotherapy. Cisplatin-induced cardiotoxicity threatens the health and life of patients, and limits the application of cisplatin. Oxidative stress is the main mechanism underlying cisplatin-induced cardiac toxicity. Luteolin (Lut) has been reported to possess cardioprotective properties by activating nuclear factor-E2-related factor 2 (Nrf2) -mediated antioxidant response. However, the effect of Lut on cisplatin-induced cardiac damage remains unclear. In this study, we revealed that Lut exerted a protective effect against cisplatin-induced cardiac dysfunction and injury in vivo. In HL-1 cells, Lut was observed to dramatically reduce cisplatin-induced apoptosis and oxidative stress by modulating the Kelch-like epichlorohydrin-associated protein 1 (Keap1)/Nrf2 pathway. Altogether, these findings suggested that Lut showed promise in attenuating cisplatin-induced cardiac injury and might be considered a protective drug candidate for chemotherapy-associated cardiovascular complications.